Investigations on Stresses in Optical Components with Spherical Surfaces - A. S. Kozeruk; Y. L. Malpica; M. I. Filonova; V. O. Kuznechik (Наука и техника)
The paper has substantiated an expediency to fix lenses with a thin center (biconcave, flat concave and negative meniscus) to a non-operational cylindrical surface. This avoids their temperature distortion at the blocking stage which is a reason for occurrence of irremovable micro and macro errors on executive surfaces of a component after its unblocking and it causes astigmatism in an image which is formed by an optical-electronic device. The paper considers a method for attachment of a lens to its side surface and it contains a design description of the device for mechanical attachment of the studied lenses during their simultaneous double-sided abrasive processing under free-grinding conditions. The paper presents a methodology for determination of a stressed state in lenses, which is based on a mathematical model of a uniform elastic isotropic deformation of a solid body. This approach takes into account a finite element method which consists in an approximation of a body under study with the help of a model presenting a set of elements with a finite number of freedom degrees which are interrelated at node points. The investigations have been executed with the purpose to study a nature of deformation distribution in a lens which made it possible to establish a directly proportional dependence of displacements in the center of the part on the magnitude of clamping forces. The paper reveals an insignificant influence of a clamping force magnitude and elastic characteristics of a lens on an optimum position of an application plane of its clamping forces. A non-contact method for monitoring errors on a polished lens surface using an interferometer with a reference front surface has been proposed in the paper.